Antibodies directed against integration host factor mediate biofilm clearance from nasopore. (13th May 2013) - Brandstetter, Kathleyn A.; Jurcisek, Joseph A.; Goodman, Steven D.; Bakaletz, Lauren O.; Das, Subinoy
Abstract : Objectives/Hypothesis: Intranasal resorbable packing, such as Nasopore, is commonly used during sinus surgery despite a paucity of evidence that demonstrates clinical benefit. We theorized that Nasopore supports bacterial growth and biofilm formation. The DNABII family of bacterial nucleic acid binding proteins stabilizes the extracellular polymeric substance of the biofilm, thus protecting bacteria from host defenses and traditional antibiotics. We tested the hypothesis that use of anti‐IHF antibodies in conjunction with antibiotics would enhance biofilm eradication from Nasopore. Study Design: In vitro experiments. Methods: Nontypeable Haemophilus influenzae (NTHI) biofilms were grown on Nasopore. Following 24‐hour incubation, biofilms were incubated for an additional 16 hours with either medium alone, naïve rabbit serum, rabbit anti‐IHF serum, amoxicillin/clavulanate, or anti‐IHF serum + amoxicillin/clavulanate. Computer statistics (COMSTAT) analysis was performed on images of biofilms obtained via confocal microscopy. Results: NTHI readily formed a biofilm on Nasopore. Treatment with amoxicillin/clavulanate alone mediated an increase in biomass by 92% to 6.63 μ 2 /μ 3 compared to incubation in sterile medium alone (3.46 μ 2 /μ 3 ). Treatment with anti‐IHF alone reduced the biomass by 77% to 1.29 μ 2 /μ 3 compared to incubation with naïve rabbit serum (5.53 μ 2 /μ 3 ). Anti‐IHF + amoxicillin/clavulanate reduced biomass by 88% to 0.66 μ 2 /μ 3 ( P <0.02) compared to incubation with naïve rabbit serum. Conclusion: Antibiotics alone were ineffective in eradicating NTHI biofilms that had formed on Nasopore in vitro. Anti‐IHF antibodies plus amoxicillin/clavulanate therapy synergistically reduced biofilm biomass by 88%. These data support clinical studies for the use of anti‐IHF combined with antibiotics to reduce biofilm formation on intranasal packing. Level of Evidence: N/A. Laryngoscope, 123:2626–2632, 2013